Remarks on the genus Sinocyrtaspis (Orthoptera: Tettigoniidae: Meconematinae) from China - Chang, Yan-Lin; Bian, Xun; Shi, Fu-Ming (Zootaxa, 2012)
The paper deals with two new species of the genus Sinocyrtaspis Liu, 2000 from China, namely Sinocyrtaspis brachycercus sp. nov., Sinocyrtaspis angustisulcus sp. nov., and supplements the photographs of Sinocyrtaspis spina Shi & Du, 2006. All material examined is deposited in the Museum of Hebei University.